(untitled) (Bangladesh Journal of Otorhinolaryngology, 2009)
This study was carried out to observe the role and outcome of endoscopic sinus surgery in the management of sinonasal disease. Study was done in department of ENT & Head-Neck Surgery, Dhaka Medical College, Dhaka from July 2002 to June 2004 (2 years). Sixty patients (60) were included retrospectively for this work. Main presenting symptoms of patients were nasal obstruction (78.33%), nasal discharge (73.33%), headache (51.66%) and recurrent sore throat (50%). In this series, minor complications occurred in 13.3% which includes synechiae, haemorrhage, infection and eccymosis of eye. No major complications like CSF leak, retroorbital haemorrhage, blindness were noted. Only 3 cases (5%) had severe haemorrohage. Most of the patients have got complete symptomatic relief, 5 cases had no improvement. It was concluded that functional endoscopic sinus surgery (FESS) has provided a safe and efficient method for dealing with different sinonasal disease and can be performed with high success rate for alleviation of symptoms with negligible morbidity. Key words: Functional endoscopic sinus surgery, sinonasal disease, complications. DOI: 10.3329/bjo.v14i2.3280 Bangladesh J of Otorhinolaryngology 2008; 14(2) : 46-50